1767 A survey to define the pre-hospital blood resuscitation practices of UK Air Ambulances. Issue 12 (22nd November 2022) - Barnard, Ed; Green, Laura; Woolley, Tom; Stanworth, Simon; Cardigan, Rebecca; Smith, Jason
Abstract : Aims, Objectives and Background: The use of pre-hospital blood components in the early resuscitation of patients with life-threatening bleeding is becoming more common. Understanding the national utilisation of pre-hospital blood is key to developing research strategies in these systems. The aim of this study was to report the blood resuscitation practices of UK Air Ambulances (AAs). Method and Design: Two sequential surveys were emailed to all UK AAs using the REDCap (research electronic data capture) system. Data were collected for 12 months during 2019 including: number of patients transported, timings, products carried, and number of patients transfused by aetiology. Data are reported as number (percentage), and mean (± standard deviation). Results and Conclusion: Nineteen (95.0%) AAs responded, and transported a total of 12, 170 patients to hospital during 2019. The mean pre-hospital time (999-call to hospital arrival) was 92.2 (±18.6) minutes. 18 (94.7%) AAs routinely carried blood products, including combinations of red cells, thawed plasma, freeze-dried plasma, and fibrinogen concentrate, table 1 . The mean units of red cells and plasma carried were 2.6 (±0.9) and 3.0 (±1.1) respectively. 709 (5.8%) adult patients received a prehospital transfusion, of which n=669 (94.4%) had a traumatic aetiology; n=384 (57.4%) and n=183 (27.4%) were transfused ≥2 and ≥4 units respectively. Forty adults received prehospital blood for non-traumatic aetiologies, including: n=18 vascular, n=10 gastrointestinal, n=6 obstetric, n=6 other. In addition, n=24 paediatric patients received a prehospital transfusion; n=23 (95.8%) following trauma. Fifteen (79.0%) UK AAs surveyed wanted to take part in future research investigating the effectiveness of whole blood transfusion. This survey defines current pre-hospital blood transfusion practice in the UK. The majority of AAs carry a combination of red cells and plasma, which are predominantly utilised following traumatic injury. Over three-quarters of UK AAs showed interest in participating in future whole blood research.